Faith Healing in Charismatic Christianity: Problematizing Miracle Claims from the Perspective of Suggestive Psychology and Public Health Ethics - Ricardo Pardede; Armando Sianipar; Hendrikus Gabriel Simatupang; Laoli Rumbarak; Urbanus Christianto (Kamali: Jurnal Ilmu Agama, 2026)
The phenomenon of faith healing within Charismatic Christianity is gaining traction across religious contexts and creating tensions with evidence-based medical standards, particularly when claims of miraculous healings could influence therapeutic decisions. Although widely discussed in theology and the sociology of religion, interdisciplinary studies that systematically integrate the perspectives of suggestion psychology and public health ethics remain limited. This study aims to identify the psychological mechanisms that shape subjective experiences of healing and evaluate their epistemological legitimacy and ethical implications for public health practice. This study was designed as a critical integrative literature review with a constructivist-critical paradigm that combines discourse analysis and normative bioethics analysis. Data were obtained from clinical psychology journal articles, Charismatic theology studies, and public health ethics documents, which were analyzed using interdisciplinary thematic analysis techniques with selection criteria of conceptual relevance and academic authority. The results indicate that the legitimacy of healing claims is constructed performatively through testimonial narratives, the strengthening of charismatic authority, and the intensification of collective emotions, thereby creating therapeutic expectations. Suggestion mechanisms—including the placebo effect, affective regulation, social confirmation, and attribution bias—contribute significantly to perceived improvement, although they do not always correlate with objective clinical indicators. The analysis also highlights the epistemic risks of causal misattribution and the ethical risks of delaying medical intervention, reproducing misinformation, and exploiting patient vulnerability. It concludes that faith-healing claims serve more as constructions of religious meaning than as clinical verification, necessitating institutional dialogue between religious communities and health authorities to protect public health interests without neglecting the spiritual dimension.